2012
DOI: 10.1016/j.celrep.2012.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Normal Spastin Gene Dosage Is Specifically Required for Axon Regeneration

Abstract: Summary Axon regeneration allows neurons to repair circuits after trauma, but most of the molecular players remain to be identified. As microtubule rearrangements have been observed in injured neurons, we tested whether microtubule severing proteins might play a role in axon regeneration. We found that axon regeneration is extremely sensitive to levels of the microtubule severing protein spastin. While microtubule behavior in uninjured neurons was not perturbed in animals heterozygous for a spastin null allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 43 publications
2
80
0
Order By: Relevance
“…In our previous study, we identified a link between spastin and axon regeneration, but we did not find any differences in injury-induced microtubule rearrangements between control and spastin-reduced neurons (Stone et al ., 2012). To try to understand the relationship between spastin and regeneration, we now use several different approaches.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our previous study, we identified a link between spastin and axon regeneration, but we did not find any differences in injury-induced microtubule rearrangements between control and spastin-reduced neurons (Stone et al ., 2012). To try to understand the relationship between spastin and regeneration, we now use several different approaches.…”
Section: Introductionmentioning
confidence: 70%
“…Spastin function in mature neurons is less studied, although spastin continues to be expressed in adult rats (Solowska et al ., 2008), and adult spastin mutant flies have a progressive decline in motor skills over the long term (Sherwood et al ., 2004). At the cellular level, reduction in spastin has been associated with failure of mature neurons to regenerate axons in Drosophila (Stone et al ., 2012); however, how spastin promotes regeneration is not known.…”
Section: Introductionmentioning
confidence: 99%
“…MT severing by katanin and spastin is particularly important for the formation of axonal branches and dendritic development (Yu et al, 2008). Several studies have also uncovered an important role for MT severing in the outgrowth of motor neurons, the formation of NMJs, and axon regeneration (Mao et al, 2014;Stone et al, 2012). Consistent with the axonal defects in various model systems, spastin mutations have been directly linked to axonal pathologies in the human neurodegenerative disease called hereditary spastic paraplegia (HSP) (Fink, 2013).…”
Section: Formation Of New Microtubulesmentioning
confidence: 95%
“…Recent studies in both Drosophila and mice have shown that microtubule destabilisation may be an essential part of the regrowth of axons after injury (Stone et al, 2012;Cho and Cavalli, 2012). Though a great deal of effort has been placed on understanding the extracellular milieu surrounding injured spinal cord axons (e.g., Nogo, and L1; Cohen et al, 1998;Stein and Tessier-Lavigne, 2001;WienckenBarger et al, 2004), the intrinsic growth potential of injured CST axons should also be assessed to determine if the intra-cellular mechanisms necessary to bring about appropriate axonal growth responses are in place for regeneration to happen (Harel and Strittmatter, 2006).…”
Section: Discussionmentioning
confidence: 99%